Thinking with Stories: The Potential of Narrative Inquiry for Vietnamese Education Research - Hang Minh Le (Vietnam Journal of Education)
Despite being one of the major modes of inquiry in qualitative research, much confusion remains over what distinguishes narrative inquiry from other qualitative methodologies. This paper aims to clarify and deepen the understanding of narrative inquiry among the Vietnamese educational research community, where scholarship using this methodology is still limited. Narrative inquiry is the study of human experience as it is through the form of stories. It invites scholars and readers to not only think about stories but think with stories. The article delves into the philosophical and methodological distinctions of narrative inquiry, before offering some methodological notes on data collection, analysis, and representation coming from the author’s own experience with conducting narrative research. The holistic appreciation of contextuality and relationality embedded in narrative inquiry resonates well with Vietnamese culture and philosophy. Consequently, this research methodology can be useful to advance research on the lived experience of education in Vietnam.